Analisis Strategi Pemasaran dan Kinerja Usaha Spice In Bowl di Kota Palembang - Adliah, Aminah; Adelia, Mutia; Kasih, Yulizar (Universitas Multi Data Palembang, 2025)
This study aims to analyze the marketing strategy and business performance of a food enterprise. The business offers two menu variants with innovative, practical, and eco-friendly packaging. The analysis focuses on the implemented marketing strategy, which includes digital promotion through social media and a sales system. Business performance is evaluated based on profit and loss statements and balance sheets. The analysis results show that digital promotion increases the number of orders, and the pre-order system supports operational efficiency.